Perception of Cervical Cancer Patients on their Financial Challenges in Western Kenya - Owenga, Jane A.; Nyambedha, Erick Otieno (BMC, 2018)
The number of cervical cancer cases is reported to increase among women of reproductive age in the recent past with patients facing challenges with care and management of the illness. However, little is known about the financial challenges these patients undergo in contexts such as western Kenya. This study assessed financial challenges and sources of financial assistance for cervical cancer patients in western Kenya. Methods A cross-sectional study involving 334 cervical cancer patients was conducted in Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH) in Kisumu from September 2014 to February 2015. Structured questionnaire, in-depth interview guide and key informant interview guide were used to collect data. Quantitative data was analyzed using Statistical Package for Social Scientists (SPSS) Version 20 at a statistical significance of P ≤ 0.05, descriptive statistics and crosstabulations were performed. For qualitative data, the responses were transcribed verbatim and the content was then analyzed by searching for emerging themes on the financial challenges faced by cervical cancer patients. Qualitative data was presented in textual form with verbatim reports for illustrations. Background The number of cervical cancer cases is reported to increase among women of reproductive age in the recent past with patients facing challenges with care and management of the illness. However, little is known about the financial challenges these patients undergo in contexts such as western Kenya. This study assessed financial challenges and sources of financial assistance for cervical cancer patients in western Kenya. Methods A cross-sectional study involving 334 cervical cancer patients was conducted in Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH) in Kisumu from September 2014 to February 2015. Structured questionnaire, in-depth interview guide and key informant interview guide were used to collect data. Quantitative data was analyzed using Statistical Package for Social Scientists (SPSS) Version 20 at a statistical significance of P ≤ 0.05, descriptive statistics and crosstabulations were performed. For qualitative data, the responses were transcribed verbatim and the content was then analyzed by searching for emerging themes on the financial challenges faced by cervical cancer patients. Qualitative data was presented in textual form with verbatim reports for illustrations. costs. There is a need for the Kenyan health care system to develop mechanisms for provision of financial support for cervical cancer patients.
Keywords: Cervical cancer; Financial challenges; Kenya